GAMBARAN PENGETAHUAN IBU BERSALIN TENTANG PROSES PERSALINAN KALA II DI POLINDES GRUJUGAN KECAMATAN LARANGAN KABUPATEN PAMEKASAN - Indra Dwi Febriarti; Sari Pratiwi Apidianti (Universitas Islam Madura, 2021)
Childbirth is a very stressful process because it involves two lives that must be saved, namely the mother and the child in the womb, so that this birthing mother needs a lot of preparation in the labor process starting from physical, mental and preparations that will be brought during childbirth. Based on a preliminary study in January, it was found that 80% of mothers gave birth who did not know the stage II labor process. The purpose of this study was to describe the knowledge of mothers giving birth about the stage II labor process at the Grujugan Polindes, Larangan District, Pamekasan Regency. This type of research is descriptive. The population was all pregnant women trimeser III (> 36 weeks) in March-May 2013 at the Grujugan Polindes, Larangan District, Pamekasan Regency, as many as 30 respondents by means of non probability sampling, namely total sampling. The variable of this study is the knowledge of the mother about the second stage of labor. Based on the research results, it is known that almost half of the 30 respondents (47%), namely 14 respondents have sufficient knowledge. Efforts can be made to overcome these problems. So health workers must always improve counseling and always provide information both verbally and from print and video media, as well as teach maternity and pregnant women about the process and procedures for childbirth so that mothers can apply it. .